PERADABAN DINASTI MAMLUK DI MESIR - Mundzirin Yusuf (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
Dynasty Mamluk/Mamalik is a Muslim dynasty that ever appeared in Egypt,Egypt became one of the regions of the Islamic world’s terrible Tempest due to the invasion of the Mongols, led by Hulagu Khan although Timur Lenk. This dynasty also known by the name of the Mamluk dynasty because it was founded by the slaves. The Mamluk dynasty inherited many civilizations, from the fields of Economics, science and technology (science and technology), the monuments of historic buildings, such as mosques, madrasahs, Tomb complex, a hospital and a library. He also became the saviors of Islamic civilization from destruction due to the invasion of the Mongols, Tatars, and Crusaders. Pattern his Government an oligarchy, if compared to other dynasties. Because, there are two kinds of succession of the leader change. First, the succession is not determined on the basis of descent, but on the basis of ability / competency by means of the election conducted by the amir. Second, the succession based on heredity. The purpose of this writing is to analyze the factors of the Mamluk dynasty, reign, and explain the results of their civilization. While its use is to add insight, good for researchers, as well as for the readers of this paper, in addition to that, also to add references, especially for the Civitas academic Department of Islamic history and culture (SKI). This method of writing history, which stages the include heuristics (data collection), which was done in libraries. Furthermore, verification or sources of criticism, with critics do data obtained, either internally, or externally. While the theory is the theory of the solidarity expressed by Ibn Khaldun. He argues that solidarity is the basis of sovereignty, because solidarity can bring together for the same purpose, defend themselves, and refuse or defeating enemies. In addition, the Kingdom or dynasty may be enforced with the help of solidarity so that it can avoid or defeat other groups. The Mamluk dynasty was one of the Kingdom’s extensive and powerful, that solidarity is based on religion (Islam).Keywords: Mamluk dynasty, civilisation, and invansion